Measurements of human tolerance to horizontal rotation within an MRI scanner: Towards gantry‐free radiation therapy. Issue 1 (29th December 2020) - Buckley, Jarryd G; Smith, Allan "Ben"; Sidhom, Mark; Rai, Robba; Liney, Gary P; Dowling, Jason A; Metcalfe, Peter E; Holloway, Lois C; Keall, Paul J
Abstract: Introduction: Recent advances in image guidance and adaptive radiotherapy could enable gantry‐free radiotherapy using patient rotation. Gantry‐free radiotherapy could substantially reduce the cost of radiotherapy systems and facilities. MRI guidance complements a gantry‐free approach because of its ability to visualise soft tissue deformation during rotation. A potential barrier to gantry‐free radiotherapy is patient acceptability, especially when combined with MRI. This study investigates human experiences of horizontal rotation within an MRI scanner. Methods: Ten healthy human participants and nine participants previously treated with radiotherapy were rotated within an MRI scanner. Participants' anxiety and motion sickness was assessed before being rotated in 45‐degree increments and paused, representing a multi‐field intensity‐modulated radiotherapy treatment. An MR image was acquired at each 45‐degree angle. Following imaging, anxiety and motion sickness were re‐assessed, followed by a comfort questionnaire and exit interview. The significance of the differences in anxiety and motion sickness pre‐ versus post‐imaging was assessed using Wilcoxon signed‐rank tests. Content analysis was performed on exit interview transcripts. Results: Eight of ten healthy and eight of nine patient participants completed the imaging session. Mean anxiety scores before and after imaging were 7.9/100 and 11.8/100, respectively ( P  = 0.26), and mean motion sickness scores were 5.3/100 and 13.7/100, respectively ( P  = 0.02). Most participants indicated likely acceptance of rotation if MRI were to be used in a hypothetical treatment. Physical discomfort was reported to be the biggest concern. Conclusions: Horizontal rotation within an MRI scanner was acceptable for most (17/19) participants.